2021
DOI: 10.1097/dad.0000000000002023
|View full text |Cite
|
Sign up to set email alerts
|

Orbital TFE3-Rearranged Perivascular Epithelioid Cell Tumor: A Case Report and Review of the Literature

Abstract: Perivascular epithelioid cell tumors (PEComas) are infrequent mesenchymal neoplasms that have particular histological and immunohistochemical features. Only a few cases have been described in the eye and orbit. This report presents a 28-year-old man who consulted for a painless left orbital mass. With the presumptive diagnosis of cavernous hemangioma, a surgical excisional biopsy was performed. Histopathological examination showed a well-delimited tumor composed of epithelioid cells with an eosinophilic cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…The association between orbital PEComa and TSC is rarely and poorly reported in the literature. Moreover, only a few cases of PEComa and their malignant potential have been described in the eye and orbit [12, 13]. Nair et al [12] and Feu-Basilio et al [13] reported a case of 9-year-old child with large orbital PEComa and 28 years old man with extremely rare orbital TFE3-rearranged PEComa, respectively, with no signs or family history of tuberous sclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between orbital PEComa and TSC is rarely and poorly reported in the literature. Moreover, only a few cases of PEComa and their malignant potential have been described in the eye and orbit [12, 13]. Nair et al [12] and Feu-Basilio et al [13] reported a case of 9-year-old child with large orbital PEComa and 28 years old man with extremely rare orbital TFE3-rearranged PEComa, respectively, with no signs or family history of tuberous sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, only a few cases of PEComa and their malignant potential have been described in the eye and orbit [12, 13]. Nair et al [12] and Feu-Basilio et al [13] reported a case of 9-year-old child with large orbital PEComa and 28 years old man with extremely rare orbital TFE3-rearranged PEComa, respectively, with no signs or family history of tuberous sclerosis. Another case was reported of 54 years old male with a slowly progressing painless mass of the right temporal lower lid diagnosed as begin PEComa with no history of TSC [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the 15 reported cases, 8 were found in the orbital soft tissue, 5 in intraocular structures, 1 in the eyelid, and 1 in the subconjunctiva; to our knowledge, this is the first reported case of a PEComa located in the fornix. 4,[6][7][8] The diagnosis of PEComa is typically based on histopathological and immunohistochemical features of epithelioid and spindle cells in nested, fascicular, or sheet-like growth patterns with melanocytic and myoid marker expression without cytokeratin or S-100 expression. 6 HMB-45 and melan-A/melanomaassociated antigen recognized by T cells 1 expression, which were seen in this patient's mass, are among the most sensitive melanocytic markers for the diagnosis of PEComa.…”
Section: Discussionmentioning
confidence: 99%
“…4 The categorization of RMS in subtypes has changed over the years and is currently based on clinicopathological features and genetic differences. 6,7 The most common subtype is embryonal, which accounts for about 60% to 70% of cases in children less than 10 years of age. 3 This subtype is most common in the head and neck region and genitourinary tract, 2 and accounts for about 70% of orbital RMS.…”
Section: Discussionmentioning
confidence: 99%
“…In ocular PEComa, only the first two have been reported. Adults with NONO-TFE3 8,16 were found to have two cases of ocular PEComa. Gao et al 8…”
Section: Ocular Transcription Factor E3-associated Perivascular Epith...mentioning
confidence: 99%